Pendekatan Ekosentris dalam Pengelolaan Taman Nasional Rawa Aopa Watumohai, Sulawesi Tenggara - Galeh Primadani; Tutun Seliari; Bahnur Salimin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: An Ecocentric Approach in Management of Rawa Aopa Watumohai National Park There is a lot of natural degradation due to human behavior that places the environment as an entity that meets its needs. Environmental management with an anthropocentric approach needs to start shifting to an ecocentric approach in its implementation, especially in managing conservation areas, to achieve sustainability goals. Ten New Ways is a principle of managing conservation areas in Indonesia initiated by Mr. Wiratno to build a learning organization so that conservation area management can provide benefits across generations. Rawa Aopa Watumohai National Park (TNRAW) is one of the national parks in Indonesia that applies 10 New Ways of managing its area. This study aimed to determine the application of an ecocentric approach in TNRAW through 10 New Ways of its management by placing humans as creatures who depend on and care about the environment and the universe. This study uses a qualitative descriptive method with data collection through observation and interviews. The research results show three main contexts in managing TNRAW with an ecocentric approach through 10 New Ways of conservation management. Applying 10 New Ways in TNRAW is an ecocentric approach to managing conservation areas. Through 10 New Ways to Manage Conservation Areas, it is proven that there is an increase in ecosystem selection in TNRAW. Conservation area management with an ecocentric approach benefits the community while maintaining the sustainability of the ecosystem.